Exploring the Indigenous Wisdom Reflected in Customary Sanctions in Tenganan Pegrisingan Village - Rahman, Fathor; Shanty, Wika Yudha; Krisna, Liza Agnesta; Budiono, Indro (Jurnal Cakrawala Hukum, 2025)
The traditional village of Tenganan Pegringsingan Bali cannot be separated from its customs and habits in conducting social relations, which are reflected in the “wig-a-wig,” the basic rules governing the order of community life, including the relationships between humans, humans, and the environment, and humans and their God. Violations of customary rules can disrupt the balance in either real or intangible ways, leading to sanctions being imposed on violators to restore the balance. This study aims, among others, (1) To find out how to classify customary violations in Tenganan Village. (2) To find out how to classify sanctions for customary violations in the Tenganan Village community. This study is a sociological, legal research project (also known as empirical legal research). The approach used is a descriptiveanalytical approach. The types of data used are primary data and secondary data. The data collection technique is by interview. The results of the study show that in Tenganan village, there is a classification of customary violations and forms of sanctions outlined in the wig-a-wig, and they are very effective because they are rules that have been agreed upon for generations to achieve true harmony in life.